2012
DOI: 10.14260/jemds/175
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of Diagnostic Efficacy of Ns1 Antigen Based Immunochromatographic Test With Immuno-Sorbent Assay and Its Role in Detection of Early Dengue Infection

Abstract: ABSTRACT:INTRODUCTION:Dengue is an acute viral infection with potential fatal complications. Rapid and easy diagnosis of dengue can help in patient triage and caremanagement. The detection of dengue virus NS1 antigen by rapid lateral flow tests offers a faster method to a presumptive diagnosis in the peripheral centers of developing countries like India where the laboratory has no great technological backup. MATERIALS AND METHODS: A total of 351 sera from patients suspected of having dengue virus infection wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
1
1
Order By: Relevance
“…With its high specificity (99.5%) and positive predictive value (PPV) (99.6%), they recommend the use of rapid immunochromatography test device for diagnosing a population group defined by clinical symptomatology of acute dengue infection. In concordance, our study also saw a higher specificity of 91.66% for NS1 ICT in comparison to 87.5% for NS1 ELISA as were studies by other authors (Kulkarni et al, 2011;Chakraverti et al, 2012). PPVs for both NS1 tests were below 80% but by ICT the values were higher at 79.31% whereas ELISA results was marginally lower at 73.52% in agreement with Zainah et al, (2009).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…With its high specificity (99.5%) and positive predictive value (PPV) (99.6%), they recommend the use of rapid immunochromatography test device for diagnosing a population group defined by clinical symptomatology of acute dengue infection. In concordance, our study also saw a higher specificity of 91.66% for NS1 ICT in comparison to 87.5% for NS1 ELISA as were studies by other authors (Kulkarni et al, 2011;Chakraverti et al, 2012). PPVs for both NS1 tests were below 80% but by ICT the values were higher at 79.31% whereas ELISA results was marginally lower at 73.52% in agreement with Zainah et al, (2009).…”
Section: Resultssupporting
confidence: 92%
“…In defiance of the results of the present study, no statistically significant superiority was noted in NS1 antigen detection by either the immunochromatography card or the immunosorbent assay over each other in agreement with Hang et al, (2009). Despite investigators Kulkarni et al, (2011) andChakraverti et al, (2012) having noted that there is no necessity to repeat the test once results have been declared positive by NS1 since it is a highly specific marker of dengue infection, other authors such as Osorio et al, (2010) point out variability in their sensitivity (ranging between 37% and 98.9%) attributable in part by the fact that sensitivity decreases with time after fever onset and in secondary infections. Addition of an IgM test alongside NS1 test improves the sensitivity by being complimentary to NS1 in such situations.…”
Section: Resultscontrasting
confidence: 70%
“…Kumar et al and Chakraverti et al found no significant difference in sensitivity and specificity between ICT and ELISA tests for detection of dengue infection. 46,47 Serum is the most common sample type. In DENV infections the Dengue Virus NS1 ELISA is an important early screening test, which is possible from day 1 to approximately day 18 after onset of symptoms that helps to minimize the diagnostic gap between RT-PCR and antibody positivity.…”
Section: Isothermal Amplification Methodmentioning
confidence: 99%